Non Recognizable Pattern - Loor, Miguel (post(s), 2016)
Facial recognition systems are increasingly embedded into everyday artifacts. This article examines how they operate based on preset patterns and algorithms, as well as their utility for corporate and state interests. Furthermore, this work sustains the critical argument of "No recognizable pattern", a photo series that envisages alternative digital identities, through ’cyborg imagery’, in order to generate untraceable biometric templates to outwit surveillance methods that expand in the current technological environment.